CONCEPTUAL BASES FOR THE DEVELOPMENT OF CREATIVE POTENTIAL OF MASTERS OF PRESCHOOL EDUCATION IN THE PROCESS OF PROFESSIONAL TRAINING - Iemchyk, Oleksandra (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the theoretical comprehension of conceptual approaches to the development of the creative potential of masters of preschool education in the process of professional training. The aim of this study is to analyze methodological bases for the development of creative potential of teacher’s personality. The researcher highlights the main conceptual approaches (student-centered, humanistic, activity, acmeological and systematic ones) and determines their impact on the construction of the educational process in a magistracy of higher educational institutions. It has been emphasized in the article that the construction of process of professional training of the master of preschool education ought to be based on such key ideas of learner-centered and humanistic approaches as the recognition of the student as the main active figure of the entire educational process. This means that in the organization of pedagogical process of the university it is necessary to create conditions for the transformation of the future specialist of preschool education to the subject of his own educational activity, developing the potential creative opportunities for each student and his or her full personal expression. The activity approach is one of the basic methodological approaches to the development of creative potential of master of preschool education, since creative activity is a necessary condition of the formation and development of his personality, which reaches a high level on condition that a student is included in a variety of educational, practical pedagogical and research activities. The acmeological approach means finding ways to develop the potential capabilities of future professionals to achieve professional excellence. A systematic approach is used for structural-semantic analysis of the process of development of creative potential of the master of preschool education as holistic pedagogical system with thorough consideration of the interaction between its constituent parts. The pedagogical process, organized and formed taking into account the complementation and consistency of the basic ideas of these approaches will show the significant results that reflect the development of the creative personality of the specialist of preschool education, who is able to carry out pedagogical activity at high – creative level, and is prepared to work in conditions of modern society.